Activité antibactérienne des extraits d’Ammi visnaga sur Pseudomonas aeruginosa - Bachkat, Djamila (My University, 2019)
Pseudomonas aeruginosa is an opportunistic pathogen involved in severe nosocomial infections difficult to treat, because of its multi-resistance, and its ability to form biofilm. Currently, the use of traditional medicine is widespread and acquired of increasing health and economic importance. In the present work we established a study to determine the antibacterial and antibiofilm effects of ethyl acetate and butanolic extracts and the essential oil obtained from the plant Ammi visnaga against P. aeruginosa ATCC 27853 and seven clinical isolates of the same species. The results obtained indicate that the extracts and the HE showed an antibacterial action against the tested P. aeruginosa isolates. According to our results, the MIC and CMB for butanol extract are around 6.25 mg / ml and 12.5 mg / ml respectively. For ethyl acetate extract, where MIC is equal to MBC and both are around 6.25mg / ml. In this work, we confirm that the ethyl acetate extract of Ammi visnaga showed an inhibitory effect on the biofilm formation of the P. aeruginosa tested isolates.
Keywords: P. aeruginosa; Multi-resistance; Biofilm; Ammi visnaga; Organic extracts; Essential oil; MIC; MBC